The Impact of Heterotopic Ossification on Self-Reported Outcomes After Total Hip Arthroplasty Using the Direct Anterior Approach. (4th November 2020) - Rüdiger, Hannes A.; Dittrich, Michael; Robinson, Jonathan; Mansour, Toni; Schwab, Tobias; Stadelmann, Vincent A.; Leunig, Michael
Abstract : Background: Heterotopic ossification (HO) is a known finding after total hip arthroplasty (THA) that potentially affects clinical outcomes. The incidence of HO is related to various factors, including soft-tissue trauma, postoperative medication, surgical approach, and the surgeon's experience. Because use of the direct anterior approach (DAA) is gaining popularity, we aimed (1) to determine the incidence of HO after DAA-THA and (2) to evaluate the impact of HO on patient-reported outcomes (PROs). Methods: We retrospectively reviewed 401 THAs (67 ± 10 years old, 210 men). The incidence and grade of HO were evaluated using the Brooker classification with anteroposterior and lateral radiographs. PROs were collected with use of the Oxford Hip Score (OHS) and the Core Outcome Measures Index (COMI)-Hip and were correlated with HO grades using generalized multiple regression models. Results: The incidence of HO was 29.9% on the anteroposterior radiographic views (Brooker grade 1, 14.5%; grade 2, 11.1%; grade 3, 2.7%; and grade 4, 0.57%); the lateral radiographic views detected 9% additional HO when compared with the anteroposterior radiographs alone (Brooker grade 1, 8%, and grade 2, 1%). HO was more frequent in men. The American Society of Anesthesiologists (ASA) grade, age in women, and higher body mass index (BMI) in men were associated with higher HO grades. A transverse "bikini" incision was associated with a lower rate (4%) of Brooker grades 3 and 4 HO when compared with a longitudinal incision (12%). A Brooker grade of 0 to 3 HO did not impact outcomes. Only Brooker grade-4 HO was associated with significantly worse PROs; however, pain was not affected. Conclusions: Low-grade HO after DAA-THA is not uncommon, and its rate is underestimated when anteroposterior radiographic views are evaluated without lateral views. The risk factors for developing HO in our cohort were an ASA grade of >3, male sex (especially with a high BMI), older age in women, and use of longitudinal incisions. With use of the bikini incision, patients had lower rates of severe HO, but mostly senior surgeons with more experience performed their surgery. Age, ASA grade, experience level of the surgeon, and Brooker grade-4 HO all had a significant influence on PROs. Clinically important HO (Brooker grade 4) remains rare after DAA-THR. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.